217k views
2 votes
Substitute the values of x and y into the expression -3x2 + 2y2 + 5xy - 2y + 5x2 - 3y2. Match that value to one of the numbers. What matches what I'm stuck 1. x = 0.5, y = -1/10 2. x = -1, y = -3 3. x =3/4 , y = 2/5 4. x = 0, y = 2.5 5. x = √2, y = √2 6. x = 2, y = -1 The answer thing. -1 9.17 14 -11.25 1.665 0.44

1 Answer

2 votes

Answer:

1. Putting x = 0.5, y = -1/10 gives 0.44

2. Putting x = -1, y = -3 gives 14

3. Putting x =3/4 , y = 2/5 gives 1.665

4. Putting x = 0, y = 2.5 gives - 11.25

5. Putting x = √2, y = √2 gives 17

6. Putting x = 2, y = -1 gives - 1

Explanation:

-3x2 + 2y2 + 5xy - 2y + 5x2 - 3y2

1. Putting x = 0.5, y = -1/10

-3(0.5)^2 + 2(-1/10)^2 + 5(-0.05) - 2(-1/10) + 5(0.5)^2 - 3(-1/10)^2

= -0.75 +0.02 - 0.25 +0.2 + 1.25- 0.03

= 0.44

2. Putting x = -1, y = -3

-3(-1)^2 + 2(-3)^2 + 5(3) - 2(-3) + 5(-1)^2 - 3(-3)^2

= -3 +18 +15+6+5-27

= 14

3. Putting x =3/4 , y = 2/5

-3(3/4)^2 + 2(2/5)^2 + 5(6/20) - 2(2/5) + 5(3/4)^2 - 3(2/5)^2

=- 27/16 +8/25 +30/20 -4/5 +45/16 - 12/25

= 18/16 - 24/25 + 30/20

= 18/16 - 96+150/100

= 18/16 +54/100

= 1800+ 864/1600

= 2664/1600

=1.665

4. Putting x = 0, y = 2.5

-3(0)^2 + 2(2.5)^2 + 5(0) - 2(2.5) + 5(0)^2 - 3(2.5)^2

= 12.5 - 5.0 - 18.75

= -11.25

5. Putting x = √2, y = √2

-3(√2)^2 + 2(√2)^2 + 5(√2.√2) - 2(√2) + 5(√2)^2 - 3(√2)^2

= -6 +4+10-4+19-6

= 17

6. Putting x = 2, y = -1

-3(2)^2 + 2(-1)^2 + 5(-2) - 2(-1) + 5(2)^2 - 3(-1)^2

= -12+2 -10 +2 +20 -3

= -1

User Graceanne
by
5.8k points